2021
DOI: 10.3389/fpls.2021.637685
|View full text |Cite
|
Sign up to set email alerts
|

A Major Locus on Wheat Chromosome 7B Associated With Late-Maturity α-Amylase Encodes a Putative ent-Copalyl Diphosphate Synthase

Abstract: Many wheat varieties have the potential to develop unacceptably high levels of α-amylase in the grains if exposed to a cool temperature shock or simply cool temperature during the early to middle stages of grain filling. This phenomenon is referred to as late maturity α-amylase (LMA). The enzyme persists in the grain until harvest and may result in wheat with a low Falling Number that does not meet receival and export specifications. Resistance to LMA is therefore a valuable target for wheat breeders and wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(60 citation statements)
references
References 64 publications
7
53
0
Order By: Relevance
“…At this time, the major QTL located on the long arm of 7B explains 31-42% of LMA phenotypic variance (Mrva and Mares 2001a;Derkx et al 2021). The 7B QTL has been confirmed in nine publications and identified in germplasm from genetically diverse breeding programs (Mrva and Mares 2001a;Mrva et al 2009;Emebiri et al 2010;Mohler et al 2014;Zhang et al 2014;Martinez et al 2018;Börner et al 2018;Derkx et al 2021). Fifteen minor QTL have also been identified.…”
Section: Genetic Mechanisms Of Lmamentioning
confidence: 94%
See 4 more Smart Citations
“…At this time, the major QTL located on the long arm of 7B explains 31-42% of LMA phenotypic variance (Mrva and Mares 2001a;Derkx et al 2021). The 7B QTL has been confirmed in nine publications and identified in germplasm from genetically diverse breeding programs (Mrva and Mares 2001a;Mrva et al 2009;Emebiri et al 2010;Mohler et al 2014;Zhang et al 2014;Martinez et al 2018;Börner et al 2018;Derkx et al 2021). Fifteen minor QTL have also been identified.…”
Section: Genetic Mechanisms Of Lmamentioning
confidence: 94%
“…Studies have demonstrated that LMA is a multi-genic trait, with associated QTL across all three genomes that appear to be independently effective and additive in their contribution to the LMA phenotype (Mrva and Mares 2002;Mares and Mrva 2008;Derkx et al 2021). At this time, the major QTL located on the long arm of 7B explains 31-42% of LMA phenotypic variance (Mrva and Mares 2001a;Derkx et al 2021).…”
Section: Genetic Mechanisms Of Lmamentioning
confidence: 99%
See 3 more Smart Citations